Chronic Exposure to 4-Nonylphenol Alters UDP-Glycosyltransferase and Sulfotransferase Clearance of Steroids in the Hard Coral, Pocillopora damicornis - Rougée, Luc R. A.; Collier, Abby C.; Richmond, Robert H. (Frontiers in Physiology, 2021)
The effects of the xenoestrogen 4-nonylphenol (4NP) on endocrine and metabolic homeostasis in the reef building coral, Pocillopora damicornis were investigated. The aim was to understand if ubiquitous nonylphenol ethoxylate contaminants in the marine environment result in altered homeostatic function. Coral colonies were chronically exposed (6 weeks) to a sublethal concentration (1 ppb) of 4NP and sampled over the coral’s lunar reproductive cycle. Although activity of steroidogenic enzymes (cytochrome P450 (CYP) 17, CYP 19 and 3b hydroxysteroid dehydrogenase) and the conjugation enzyme glutathione-S-transferase was not altered, significant increases in the activity of the steroid clearing enzyme UDP-glucuronyl sulfotransferase (UGT) were observed. The natural fluctuation of UGT activity with the lunar cycle was replaced with consistently high UGT activity throughout the reproductive cycle during 4NP exposure. No effect of 4NP on the reverse reaction, mediated by b-glucuronidase, was observed. Thus, 4NP shifts the UGT:b-glucuronidase ratio towards greater clearance at points in the lunar cycle where retention of compounds is typically favored. Additionally, 4NP reduced activity of the steroid regeneration enzyme steroid sulfatase, further shifting the system towards clearance rather than regeneration. These data imply that environmentally relevant levels of 4NP may be impacting the reproductive health of corals and threatening the persistence of coral reefs.